2004
DOI: 10.1111/j.0001-6349.2004.0298.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between umbilical and maternal serum adiponectin levels and neonatal birthweights

Abstract: The levels of adiponectin were higher in umbilical cord serum than in maternal serum. Moreover, the adiponectin levels in umbilical cord serum were found to correlate positively with neonatal birthweights. Therefore, fetal adiponectin, not maternal serum adiponectin, may be involved in fetal development during late pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
74
4
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 12 publications
12
74
4
2
Order By: Relevance
“…Furthermore, umbilical vein serum adiponectin levels were three-fold higher than maternal serum adiponectin levels in normal pregnancy [14]. When adiponectin levels were measured in cord vein, a striking increase in plasma adiponectin concentrations with gestational age was noted [15]; concentrations at term were more than 20-fold higher compared with 24 weeks of gestation [15].…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, umbilical vein serum adiponectin levels were three-fold higher than maternal serum adiponectin levels in normal pregnancy [14]. When adiponectin levels were measured in cord vein, a striking increase in plasma adiponectin concentrations with gestational age was noted [15]; concentrations at term were more than 20-fold higher compared with 24 weeks of gestation [15].…”
Section: Introductionmentioning
confidence: 88%
“…Maternal adiponectin has a high molecular weight; therefore, it probably does not pass through the placental barrier; its concentration in the umbilical cord is of fetal origin (14,15). The origin of adiponectin in the fetus is not clearly understood (13).…”
Section: G Estational Diabetes Mellitus (Gdm) Is Impairedmentioning
confidence: 99%
“…In adults, adiponectin concentration is inversely related to adiposity, but its association with adiposity is poorly understood (9,11,13). Some studies indicate a positive correlation between cord plasma adiponectin concentration and adiposity in infants (8,12,14,(16)(17)(18)(19)(20) and some have found no significant correlation (9,15).…”
Section: G Estational Diabetes Mellitus (Gdm) Is Impairedmentioning
confidence: 99%
“…6,7 Some investigators have reported a significant positive relationship between birth weight, as a proxy mirror of the intrauterine environment, and cord blood adiponectin levels. [8][9][10] Our previous study demonstrated that the serum adiponectin levels on the first day of life were significantly higher in appropriate-for-gestational-age birth weight (AGA) than in small-for-gestational-age birth weight (SGA) term neonates. 11 Although adiponectin levels in the cord blood of term infants are extensively higher than in children or adults, its exact physiological role in regulating intrauterine fetal growth has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…11 Although adiponectin levels in the cord blood of term infants are extensively higher than in children or adults, its exact physiological role in regulating intrauterine fetal growth has not been fully elucidated. 8,9,12 On the other hand, epidemiological studies have revealed that there is a relationship between fetal growth retardation and the subsequent development of insulin resistance later in life. 13,14 Single-nucleotide polymorphisms (SNPs) in the adiponectin gene (ADIPOQ) have been associated with adiponectin levels, changes in insulin sensitivity and risk for type 2 diabetes mellitus and coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%